Impact Computation of electric and magnetic field on farmers working near high voltage transmission lines in Pakistan by developing software - Basit Ali; Aqsa Shafqat; Saman Abbasi; Kaniz Fatima (Penerbit Universiti Kebangsaan Malaysia, 2023)
In this revolutionized era, electricity has become an essential necessity of humans. People all over the world are concerned about the effects of HVTL (high voltage transmission lines) and their severe effects impacting on their health. Over the last two decades, developed countries have become increasingly concerned about an increase in electromagnetic fields, which poses health risks. The electromagnetic field emitted by HVTL will cause a low current to pass through the bodies. The electricity system produces low frequency electromagnetic field, which lead to the health hazards. The critical problem to those who are living near HVTL, therefore our fundamental task is to let them aware of the risk. Due to harmful exposures of electric and magnetic field, farmers working under HVTL or having their residences, suffering through severe effects in the form of different diseases. The main aim behind this research is to design GUI based software having two parts which helps to bring output of the electromagnetic field exposures with the help of various parameters includes different weather conditions affecting electric field, how people of different ages are being affected through it, identification of the regions need further protection by developing a proper mathematical model. Two approaches were used, one is to interface GUI with different sensors and second is user define function. On the basis of output EMF it will be able to find out the possible disease by using the data of WHO, ICNIRP and the data which is collected from surveys of different regions.